2005
DOI: 10.2135/cropsci2004.0187
|View full text |Cite
|
Sign up to set email alerts
|

Dinitroaniline‐Induced Genetic Changes in Bermudagrass

Abstract: golf putting green turf in the southern USA through greatly improved playability characteristics as well as Off-type bermudagrasses (Cynodon spp.) continue to be a major much-needed uniformity by way of planting a singleconcern on southern U.S. golf greens because of the disruption of surface source cultivar. Uniformity in these vegetatively propauniformity and playability. The current study was undertaken to measure the genetic stability of six bermudagrass cultivars (Champion, Floradwarf, gated turf cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…While TifEagle was reported to be derived from Tifway II (Hanna and Elsner 1999); Harris-Shultz et al (2010) and Zhang et al (1999), both suggested that TifEagle may have been derived from Tifgreen (or a Tifgreen related plant) due to the high dissimilarity coefficients reported between TifEagle and Tifway II using amplified fragment length polymorphism (AFLP) methodology. Findings of Capo-chichi et al (2005) and Chen et al (2009) further support this assertion in that both research teams reported a high degree of genetic similarity between TifEagle and Tifgreen. TifEagle is a vegetatively propagated cultivar reported to produce higher quality putting surfaces than Tifdwarf when mowed daily at 4 mm or less.…”
Section: History Of Bermudagrass Development For Putting Greensmentioning
confidence: 79%
See 4 more Smart Citations
“…While TifEagle was reported to be derived from Tifway II (Hanna and Elsner 1999); Harris-Shultz et al (2010) and Zhang et al (1999), both suggested that TifEagle may have been derived from Tifgreen (or a Tifgreen related plant) due to the high dissimilarity coefficients reported between TifEagle and Tifway II using amplified fragment length polymorphism (AFLP) methodology. Findings of Capo-chichi et al (2005) and Chen et al (2009) further support this assertion in that both research teams reported a high degree of genetic similarity between TifEagle and Tifgreen. TifEagle is a vegetatively propagated cultivar reported to produce higher quality putting surfaces than Tifdwarf when mowed daily at 4 mm or less.…”
Section: History Of Bermudagrass Development For Putting Greensmentioning
confidence: 79%
“…The repeated use of pesticides and plant growth regulators (PGR) could potentially influence aneuploidy (Karp 1994; Capo-chichi et al 2005; Gadeva and Dimitrov 2008). Capo-chichi et al (2005) reported that chronic exposure of Champion Dwarf bermudagrass in greenhouse culture to the dinitroaniline herbicides, pendimethalin, and oryzalin, induced the formation of four off-type grasses.…”
Section: The Genetic Instability Of Commercial Cultivars Leading To Omentioning
confidence: 99%
See 3 more Smart Citations